Anatomic influence of sugarcane biomass on xylan solubilization - Melati, Ranieri Bueno [UNESP]; Sass, Daiane Cristina [UNESP]; Pagnocca, Fernando Carlos [UNESP]; Brienzo, Michel [UNESP] (Elsevier, 2021)
Sugarcane biomasses, such as bagasse and straw, are abundant and represent renewable sources for the production of molecules of economic interest, such as xylan. However, the solubilization methods for this macromolecule face the material recalcitrance and, consequently, need a higher amount of chemicals. This study brings as the fractioning of biomass for xylan extraction, aiming to verify how the recalcitrance of different segments of the plant may interfere with the process of xylan solubilization. Hydrogen peroxide was applied in the xylan solubilization starting from the bagasse, moving on to the leaf and stem, which was fractionated in internode, node, and external fraction (which contains epidermis). The solubilized xylan was evaluated as a substrate for the determination of the enzymatic activity of xylanase. The solubilized xylan was monitored for its solubility and for impurities, such as salt and residual lignin content. The results of xylan solubilization with 6 % of hydrogen peroxide were 86.28, 65.39, 76.78, 97.95, 96.48 %, successively for bagasse, internode, node, external fraction, and leaf. With the application of 3% peroxide, the yield decreased to lower than 30 %, except for the internode and the leaf, which showed 47.85 and 46.15 %, respectively. The RMN analysis suggested similarity among the xylan samples solubilized from the different sugarcane anatomic fractions. The highest enzymatic activities were found with the solubilized xylan, instead of the commercial one. The solubility and purity tests (low salt content) indicate that the solubilized xylan presented characteristics similar to commercial xylan or even better than it.
Keywords: Biomass; Hydrogen peroxide; Lignin; Sugarcane; Xylan; Xylanase